(untitled)
By using the hypergeometric function defined by the Dziok-Srivastava operator, a new subclass of meromorphic function is introdued. We obtain Fekete-Szegö inequalities for the meromorphic function f(z) for which α-1+α{1+z[_lI_mf(z)]''[_lI_mf(z)]'z[_lI_mf(z)]'_lI_mf(z) φ (z) (αC-{12, 1}). , number=2, journal=Communications in Mathematical Research, year=2019, month=Dec., pages=184–192